2021
DOI: 10.21608/edj.2021.67349.1548
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Alveolar Ridge Augmentation Using Xenogenic Bone Graft: A Comparison Between the Flap and Subperiosteal Tunneling Techniques

Abstract: Background:The aim of this study was to evaluate the prognosis of minimal invasive horizontal alveolar ridge augmentation using small incision and subperiosteal tunneling technique.Methods: This study was conducted on 10 partially edentulous patients with horizontal alveolar bone deficiency in 12 areas that need horizontal alveolar ridge augmentation for future implant placement. Cone beam computer tomography was done for sites that need implant placement preoperatively. Xenogeneic bone was used for grafting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…versus open flap technique in 10 patients with horizontal ridge defects. Six months postop, it was observed that the healing was better in the minimally invasive subperiosteal tunneling group [21].…”
Section: Hamed Et Al Compared Minimally Invasive Horizontal Ridge Augmentation With Subperiosteal Tunnelingmentioning
confidence: 92%
“…versus open flap technique in 10 patients with horizontal ridge defects. Six months postop, it was observed that the healing was better in the minimally invasive subperiosteal tunneling group [21].…”
Section: Hamed Et Al Compared Minimally Invasive Horizontal Ridge Augmentation With Subperiosteal Tunnelingmentioning
confidence: 92%